2016
DOI: 10.1128/aac.02516-15
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum-Cephalosporin Resistance Genes in Escherichia coli from Beef Cattle

Abstract: e R esistance to extended-spectrum cephalosporins (ESC) has rarely been detected in Enterobacteriaceae from beef cattle in Canada (1); in contrast, in the United States, it has repeatedly been found in bacteria from cattle (see, for instance, references 2 to 5). To assess whether similar bacteria are present in beef cattle in Alberta, Canada, we used enrichment cultures and PCR to increase the sensitivities of our detection methods.Four hundred thirty-two composite fecal samples were collected from 73 pens in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
5
17
0
Order By: Relevance
“…CTX‐M‐15 is the most frequently identified CTX‐M enzyme in both human clinical isolates (Castanheira et al., ) and companion animals in the US (Canton et al., ). This sequence type has been rarely reported in food animals, found in the enteric flora of dairy cows on 4% of Ohio herds (Mollenkopf et al., ) and swine flora from 2% of US finishing barns (Mollenkopf et al., ); however, a more recent study reported a higher prevalence of CTX‐M‐15 (7%) compared to CTX‐M‐1(0) in isolates from North American beef feedlot cattle, suggesting a transmission from humans to animals (Cormier et al., ). The 2010 SENTRY Antimicrobial Surveillance Program reported that 6 of the 85 CTX‐positive Enterobacteriaceae from 26 US hospitals carried CTX‐M‐27(Castanheira et al., ), similar to the rate in beef feedlot cattle (7% of CTX isolates) (Cormier et al., ), and it was the predominant sequence type found recently on one Ohio dairy (Mathys et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…CTX‐M‐15 is the most frequently identified CTX‐M enzyme in both human clinical isolates (Castanheira et al., ) and companion animals in the US (Canton et al., ). This sequence type has been rarely reported in food animals, found in the enteric flora of dairy cows on 4% of Ohio herds (Mollenkopf et al., ) and swine flora from 2% of US finishing barns (Mollenkopf et al., ); however, a more recent study reported a higher prevalence of CTX‐M‐15 (7%) compared to CTX‐M‐1(0) in isolates from North American beef feedlot cattle, suggesting a transmission from humans to animals (Cormier et al., ). The 2010 SENTRY Antimicrobial Surveillance Program reported that 6 of the 85 CTX‐positive Enterobacteriaceae from 26 US hospitals carried CTX‐M‐27(Castanheira et al., ), similar to the rate in beef feedlot cattle (7% of CTX isolates) (Cormier et al., ), and it was the predominant sequence type found recently on one Ohio dairy (Mathys et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Faecal (Velasova et al, 2019) Infection (Hunter et al, 2010) ND (Stokes, 2014) Czech Republic Faecal (Dolejska et al, 2011b) Sick (Dolejska et al, 2013) R eunion ND (Gay et al, 2018) Slovakia Faecal (Kme t and Buj n akov a, 2018) Sweden Faecal (Duse et al, 2015) Switzerland Faecal (Endimiani et al, 2012;Geser et al, 2012a;Zurfluh et al, 2015) Turkey Faecal (AslantaŞ et al, 2017;Pehlivanoglu et al, 2016) North America Canada ND (Cormier et al, 2019) USA Faecal (Mir et al, 2016;Mollenkopf et al, 2012;Wittum et al, 2010) Asia China Mastitis (Ali et al, 2016(Ali et al, , 2017 South Korea Mastitis (Tark et al, 2017) Indonesia Faecal (Sudarwanto et al, 2016) Japan Mastitis (Ohnishi et al, 2013b) Klebsiella pneumoniaeEurope Italy Mastitis (Locatelli et al, 2010) Klebsiella ozaenae Italy Faecal (Stefani et al, 2014) Salmonella enterica Germany ND (Rodríguez et al, 2009) CTX-M-1/61 E. coli Europe Germany Faecal (Dahms et al, 2015) CTX-M-2 E. coli South America Brazil Faecal (Palmeira et al, 2018) Europe Germany Mastitis (Eisenberger et al, 2017;Freitag et al, 2017;Michael et al, 2017) Sick (Michael et al, 2017) Netherlands Faecal (Ceccarelli et al, 2019;Heuvelink et al, 2019) North America Canada Faecal (Cormier et al, 2016) Asia Japan Faecal (Shiraki et al, 2004) Diarrheic (Ohnishi et al, 2013a) Infection (Asai et al, 2011) K. pneumoniae Japan Mastitis (Ohnishi et...…”
Section: Ctx-m-1mentioning
confidence: 99%
“…In North America only 2 countries registered E-ESBL description in cattle, Canada and the United States, the last one being the world's largest cattle producer (USDA et al, 2017). CTX-M-15, CTX-M-32 and CTX-M-65 were the only beta-lactamases described in both countries, the Figure 3 shows the complete described ESBL from cattle in the North America (Cormier et al, 2016;Mir et al, 2016;Poole et al, 2017;Tate et al, 2017).…”
Section: North Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Tetracyclines, penicillins, and aminoglycosides were introduced in the 1940s and macrolides in the 1970s ( 40 ). Consequently, multiple genes encoding various degrees of susceptibility to these drug classes have been observed in fecal E. coli and S. enterica isolates from farm animals ( 41 45 ). The tetracycline resistance gene pool is especially diverse, with several tens of tet genes described to date for different animal and human hosts ( 41 , 46 ).…”
Section: Discussionmentioning
confidence: 99%